Status of hepatitis C virus vaccination: Recent update - Abdelwahab, Kouka Saadeldin (World J Gastroenterol, 2016)
Hepatitis C virus (HCV) infection is still a major public health problem worldwide since its first identification in 1989. At the start, HCV infection was post-transfusion viral infection, particularly in developing countries. Recently, due to iv drug abuse, HCV infection became number one health problem in well-developed countries as well. Following acute HCV infection, the innate immune response is triggered in the form of activated coordinated interaction of NK cells, dendritic cells and interferon α. The acquired immune response is then developed in the form of the antibody-mediated immune response (ABIR) and the cell-mediated immune response (CMIR). Both are responsible for clearance of HCV infection in about 15% of infected patients. However, HCV has several mechanisms to evade these antivirus immune reactions. The current review gives an overview of HCV structure, immune response and viral evasion mechanisms. It also evaluates the available preventive and therapeutic vaccines that induce innate, ABIR, CMIR. Moreover, this review highlights the progress in recent HCV vaccination studies either in preclinical or clinical phases. The unsatisfactory identification of HCV infection by the current screening system and the limitations of currently available treatments, including the ineligibility of some chronic HCV patients to such antiviral agents, mandate the development of an effective HCV vaccine.